2018
DOI: 10.1002/mnfr.201800079
|View full text |Cite
|
Sign up to set email alerts
|

Cruciferous Vegetables, Isothiocyanates, and Bladder Cancer Prevention

Abstract: Bladder cancer is a significant health burden due to its high prevalence, risk of mortality, morbidity, and high cost of medical care. Epidemiologic evidence suggests that diets rich in cruciferous vegetables, particularly broccoli, are associated with lower bladder cancer risk. Phytochemicals in cruciferous vegetables, such as glucosinolates, which are enzymatically hydrolyzed to bioactive isothiocyanates, are possible mediators of an anticancer effect. In vitro studies have shown inhibition of bladder cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(94 citation statements)
references
References 177 publications
2
81
0
6
Order By: Relevance
“…Isothiocyanates like SFN and erucin have been shown to inhibit the growth of neoplastic bladder cells. Moreover, the enhanced bioavailability of isothiocyanates has shown a better chemopreventive effect in an animal model of bladder cancer (Abbaoui, Lucas, Riedl, Clinton, & Mortazavi, ; Kumar et al, ; Mitsiogianni et al, ).…”
Section: Some Common Phytochemicals With Chemopreventive and Chemothementioning
confidence: 99%
“…Isothiocyanates like SFN and erucin have been shown to inhibit the growth of neoplastic bladder cells. Moreover, the enhanced bioavailability of isothiocyanates has shown a better chemopreventive effect in an animal model of bladder cancer (Abbaoui, Lucas, Riedl, Clinton, & Mortazavi, ; Kumar et al, ; Mitsiogianni et al, ).…”
Section: Some Common Phytochemicals With Chemopreventive and Chemothementioning
confidence: 99%
“…Leukemia [87,124,[175][176][177][178][179] Prostate cancer [91,95,[180][181][182] non-small cell lung cancer cells [107,183,184] Pancreatic cancer [165,[185][186][187] Breast cancer [92, 93, 101-103, 105, 108, 109, 188-195] Bladder cancer [169,[196][197][198][199][200][201] Ovarian cancer [99] HepG2 Carcinoma Cells [202][203][204][205][206] Gastric cancer [207,208] Squamous cell carcinoma [209,210] Nasopharangeal cancer [211] Melanoma [212] Glioma [173,[213][214][215] Colon cancer [110,216,217] Lung cancer [218,219]...…”
Section: Cancer Type Refmentioning
confidence: 99%
“…Sinapis nigra L. or the black mustard is a plant cultivated mostly for food and medicinal purposes. It belongs to the Brassicaceae family and is native and grown in arid and semi-arid areas of the world where the drought and salinization can adversely affect the growth and quality of cultivated plants which can eventually decrease their yield and economic value (Abbaoui et al, 2018). In recent decades, the problem of salinization is aggravated by climate change and the use of highly mineralized irrigation water as well as improper soil management (Taiz and Zeiger, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the Brassicaceae family became a focus on the growing interest as studies have shown that high consumption of green parts (shoot) and seeds of these crops reduces the risk of a great number of health problems (Abbaoui et al, 2018). The high consumption level of Sinapis herb reduces the risk of a great number of cancers, particularly cancers of the gastrointestinal tract, lung, bladder and prostate (Johnson, 2018).…”
Section: Introductionmentioning
confidence: 99%